Le costanti del potere e gli exempla imitanda ottavianei - Fenocchio, Marco Antonio (Cultura giuridica e diritto vivente, 2016)
[The constants of power and Octavian’s exempla imitanda] Political, social and juridic powers throughout history show many constant factors, which can hardly be concealed in narrative and counter-narrative lores, as proven hugely by historical reports about Rome’s first emperor. The whole host of personal informations about Augustus treasured in Suetonian De vita Caesarum gives in this regard an admirable and truly paradigmatic example. Cunning creation of a new institutional set-up was always poised between moralising resolutions and somewhat contradictory politics and life-styles implemented in practice.